Dopaminergic activation anticipates daily nursing in the rabbit. (26th April 2017) - Aguirre, J.; Meza, E.; Caba, M.
Abstract: Maternal care is a motivated behavior and in the rabbit it is restricted to the spontaneous return of the mother to nurse her pups for just a few minutes once a day. Previously we have reported neural activation of brain areas and neuroendocrine cells after nursing. However, this daily spontaneous return suggests that the mother is in a high motivational state to nurse her pups. Here we hypothesized that during anticipation of nursing there is an activation of dopaminergic neurons of the mesolimbic system and in their target areas. Then we explored, by the expression of FOS protein, possible activation of the mesolimbic system as well as dopaminergic cells of the A10 cell group before and after nursing and in control does. Additionally, we measured FOS expression in the preoptic area and lateral septum. We found a significant increase of FOS before nursing, and a further increase after nursing, in the mesolimbic system and dopaminergic cells as well as in the preoptic area and lateral septum. Interestingly, the medial prefrontal area shows an intense activation during anticipation of nursing, which remains after nursing. We conclude that the activation of the mesolimbic system before nursing is related to the high locomotor behavior prior to the next nursing bout and support the proposal that the mother is in a high motivational state at the time of returning to the nest. The additional activation after nursing can be related to the neuroendocrine and neural consequences of the milk ejection reflex by suckling. Abstract : Maternal care in the rabbit it is restricted to the spontaneous return of the mother to the nest once a day to nurse her pups for just a few minutes. Here we report an increase in maternal locomotor behavior and in the dopaminergic mesolimbic system and their target areas at the time of nursing. Our results suggest that the mother is in a high motivational state at the time of returning to the nest and that the dopaminergic system is important for the timing of daily nursing.